Effect of ADEEM methods (Assess, Do Massage Frirage, Exercise ROM, Evaluation, Making Schedule) on increasing muscle strength upper extremity of ischemic stroke patients at RSU GMIM Pancaran Kasih Manado - Noviyanti Parapaga; Fery Mendrofa; Julvainda Eka (Jurnal Ners dan Kebidanan Indonesia)
Background : A stroke is when the blood supply to part of the brain stops, causing an inability to carry out central nervous system (CNS) tasks. In stroke patients, 70-80% experience hemiparesis (muscle weakness) as a result of motor neuron disorders. The ADEEM method as a rehabilitation intervention for post-stroke patients aims to increase muscle strength consisting of Asses, Do Massage Frirage, Exercise ROM, Evaluation & Making Schedule. Objectives : This study aims to determine the effect of the ADEEM Method on increasing muscle strength in ischemic stroke patients. Methods : The type of research is quantitative research with a pre-experimental design of one group pre post test. The population of this study was ischemic stroke patients with a stroke duration of > 3 months as many as 37 respondents. Respondents were given the ADEEM Method intervention for 45 minutes with meetings 2-3 times a week for 2 weeks. The instrument used to assess muscle strength is the Manual Muscle Test Observation Sheet. The validity and reliability tests of the instruments obtained reliability coefficient values of α > 0.63 to 0.98 for individual muscle groups, and α > 0.57 to 1.0 for total MMT scores. The validity value of MMT showed r = 0.768 (>0.05). Results : This study was analyzed using univariate analysis (frequency distribution) and bivariate analysis (saphiro wilk normality test and Wilcoxon test) with significance. Wilcoxon test results obtained ρ value <0.05 (0.003), this means that there is an effect of the ADEEM Method on increasing muscle strength in ischemic stroke patients. Conclusions : ADEEM method as one of the practical methods to increase muscle strength for ischemic stroke patients. This method can be done by nurses and family members in caring for ischemic stroke patients.